2004
DOI: 10.1097/01.ju.0000116546.06765.d1
|View full text |Cite
|
Sign up to set email alerts
|

Is Antegrade Stenting Superior to Retrograde Stenting in Laparoscopic Pyeloplasty?

Abstract: Laparoscopic stenting is a simple technique that obviates the need for an additional procedure and decreases the risk of the stent being cut or migrating upward. It also provides better anatomical delineation and dissection around the ureteropelvic junction since the pelvis remains distended. In addition, it makes suture placement and knot tying easy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 11 publications
1
55
0
Order By: Relevance
“…Mandhani and colleagues reported laparoscopic pyeloplasty with antegrade stent insertion in 24 patients [Mandhani et al 2004]. This approach avoids the need to reposition the patient and, once mastered, can be performed in less than 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Mandhani and colleagues reported laparoscopic pyeloplasty with antegrade stent insertion in 24 patients [Mandhani et al 2004]. This approach avoids the need to reposition the patient and, once mastered, can be performed in less than 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Since LP started to get popularized within the last 2 decades, the surgical steps of the procedure have been the subject of numerous publications [6,7,8,9,10]. Of the surgical steps that affects the operative time and success, stenting is another critical step of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Mandhani et al [6] compared the 2 different approaches of stenting during LP. Antegrade stenting was successfully performed in 23 out of 24 patients in a mean time of 5.2 min, while the time required for retrograde stenting was 39.3 min.…”
Section: Discussionmentioning
confidence: 99%
“…Complications due to JJ stenting that occur during insertion or due to the presence of the JJ stent in situ are described in the literature. [16] Mandhani et al [5] recognized inadvertent injury to the ureterovesical junction.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic antegrade JJ stenting diminishes the need for an additional procedure and decreases the risk of complications, such as the stent being cut or migrating upward. [5] Moreover, antegrade JJ stenting provides better anatomical delineation and dissection around the ureteropelvic junction (UPJ) since the renal pelvis remains distended. However, Papalia et al [6] reported that retrograde JJ stenting was a favorable technique with a high success rate.…”
Section: Introductionmentioning
confidence: 99%